Odpowiedzi

Najlepsza Odpowiedź!
2010-03-22T15:21:00+01:00
Rozwiązanie w załączniku ;)
2010-03-22T15:24:23+01:00


4) (x+1)kwadrat - 3x= x kwadrat +4
x²+2x +1 -3x= x²+4
-x = 3
x = 3
2010-03-22T15:26:35+01:00
1) 2* 3+x/4= 5(x-2)
6+x/4=5x-10| *4
24+x=20x-40
-19x=-64
x=3i 7/19
2) 3x- 1/4+ 2x=x+8
4x=7i 3/4
x=1i 15/16
3) 4(x-2)/3 - 2(x-1)/2=2x|6
8(x-2)-6(x-1)=12x
8x-16-6x+6=12x
-10=10x
x=-1
4) (x+1)kwadrat - 3x= x kwadrat +4
xkwadrat +2x+1-3x=xkwadrat+4
-x=3
x=-3
5) 2(x+2)kwadrat /4= xkwadrat +2
2(xkwadrat +4x+4)/4=xkwadrat +2
2xkwadrat+8x+8/4=xkwadrat+2|4
8xkwadrat+32x+32=4xkwadrat+8
4xkwadrat+32x=-24
6) 1/7- 2* 1/14=2x
1/7-1/7=2x
2x=0
x=0
7) 3(1-2x)> 4x
3-6x>4x
-10x>-3
x<3/10